Military diplomacy and Russia’s policy in Syria - T. V. Verbitskaia (Сравнительная политика, 2017)
The article is devoted to the study of problematic issues of the change of modern international relations system. It was found that such changes have affected the very essence of international relations: actors (the emergence of non-governmental actors, the importance of which is increasing), methods (the scope of military diplomacy has been expanded), objects (the nature of armed confl icts, both international and non-international, has been changed; the concept of international crime is determined by the danger posed to the international community). The author sets time frameworks of the changes, studies the characteristics of international system and its elements. The study focuses on the phenomenon of military diplomacy and criteria of its effectiveness. These criteria for the effectiveness of military diplomacy are applied to the Russia’s actions in Syria as part of its fi ght against international terrorism. The key documents of cooperation between the Russian Federation and the Syrian Arab Republic are analyzed. The research is focused on Russian measures in its war against terror in Syria. The author posits that Russia’s actions in Syria represent a model which refl ects the role of non-governmental actors in world politics, the methods used in international affairs and the specifi cs of international crimes.